2012
DOI: 10.1016/j.rbp.2012.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric disorders among individuals who drive after the recent use of alcohol and drugs

Abstract: The results of this study can aid in the design of interventions, treatment programs and focused psychiatric evaluations, both in Brazil and abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…Literature suggests that the DUI population comprises heterogeneous clusters of individuals, especially when it comes to psychiatric comorbidity (Freeman et al, 2011;Karjalainen et al, 2013;LaPlante et al, 2008). In general, individuals with history of DUI present higher prevalence of psychiatric disorders including depression, anxiety, and post-traumatic stress (Faller et al, 2012;Lapham et al, 2006;Pogue et al, 2017). The association of BD and DUI presented here has been already reported in the literature under the hypothesis that during manic and hypomanic states individuals with BD tend to present impulsive and risk-taking behaviors (Albanese et al, 2010;Freeman et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…Literature suggests that the DUI population comprises heterogeneous clusters of individuals, especially when it comes to psychiatric comorbidity (Freeman et al, 2011;Karjalainen et al, 2013;LaPlante et al, 2008). In general, individuals with history of DUI present higher prevalence of psychiatric disorders including depression, anxiety, and post-traumatic stress (Faller et al, 2012;Lapham et al, 2006;Pogue et al, 2017). The association of BD and DUI presented here has been already reported in the literature under the hypothesis that during manic and hypomanic states individuals with BD tend to present impulsive and risk-taking behaviors (Albanese et al, 2010;Freeman et al, 2011).…”
Section: Discussionsupporting
confidence: 70%
“…This study is one of the few national studies to consider the depression as a predictor of DUIA in Brazilian drivers. A road survey conducted in Brazil found a high prevalence (19.4%) of depression among drivers with positive BAC [56]. A cross-sectional telephone study of 3979 adults in Ontario (Canada) showed that the probability of DUIA within the previous 12 months increased significantly with an increase in the depressed mood [57].…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest that individuals with different drug consuming patterns may present not only different individual characteristics but tend to cluster in different settings, as discussed in Maxwell's study (2012), carried out in Texas, US. Additional, unmeasured, variables, such as psychiatric comorbidity or other medical conditions (such as type 1 diabetes) are likely to be associated with both substance misuse and accidents, and should be further explored (Faller et al, 2012).…”
Section: Discussionmentioning
confidence: 99%